2006
DOI: 10.1111/j.1540-8175.2006.00305.x
|View full text |Cite
|
Sign up to set email alerts
|

Tricuspid Annular Systolic Velocity: A Useful Measurement in Determining Right Ventricular Systolic Function Regardless of Pulmonary Artery Pressures

Abstract: Assessment of right ventricular (RV) systolic function can be somewhat difficult, particularly in pulmonary hypertension (PH). RV fractional area change (FAC) and tricuspid valve annular motion (TAPSE) although useful in the assessment of RV performance, their use can be sometimes limited and tedious. Thus, a quicker but yet reliable alternative is needed. Accordingly, we compared peak tricuspid annulus systolic (TA Sa) velocities derived from Doppler tissue imaging (DTI) with both RVFAC and TAPSE to estimate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
202
2
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(220 citation statements)
references
References 32 publications
8
202
2
3
Order By: Relevance
“…14,15 There has been a wide range of correlations between TAPSE and other measures of RV function. Good correlations were obtained comparing TAPSE with RVEF, [16][17][18][19][20] and better correlations were obtained comparing TAPSE with RV fractional area of change 6,12 and global RV strain. 21 Correlations were more modest when compared with RVEF using magnetic resonance imaging.…”
Section: Discussionmentioning
confidence: 89%
“…14,15 There has been a wide range of correlations between TAPSE and other measures of RV function. Good correlations were obtained comparing TAPSE with RVEF, [16][17][18][19][20] and better correlations were obtained comparing TAPSE with RV fractional area of change 6,12 and global RV strain. 21 Correlations were more modest when compared with RVEF using magnetic resonance imaging.…”
Section: Discussionmentioning
confidence: 89%
“…Tricuspid annular descent or TAPSE has been shown to correlate with RV FAC, but is influenced by LV function. 4,5,7 Values above 20 mm have been associated with normal biventricular function. 5 The pre-ejection period has also been used to assess right-heart function using variables such as dP/dt.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Tricuspid annular or myocardial velocities (TAV) have also been used to assess RV function. 7,8 The isovolemic acceleration (IVA) has been shown to be a load-independent measure of contractility. 9 The systolic ejection velocity has compared favourably with other measures of RV function but remains a more loaddependent measure of contractility.…”
Section: Résumémentioning
confidence: 99%
“…Previous studies reported that a TAPSV < 11.5 cm/s or < 10.5 cm/s was able to predict impaired right ventricular systolic function. 5,13) A similar cutoff (TAPSV < 10.8 cm/s) was found in adults as a predictor of 14)…”
Section: Discussionmentioning
confidence: 85%